Transformasi Ketrampilan Furniture Tukang Kayu: Program Pelatihan Smart Furniture di Bengkel Kayu Mitra Kota Malang - Arifin, Achmad Saiful; Ramadhani, Viola Malta; Amin, Rais; Nurhida, Ika Salsabila (Universitas Tribhuwana Tunggadewi Malang, 2025)
The Sukun, Lowokwaru, and Karangbesuki areas of Malang City are known for their supply of construction workers, the most significant proportion being carpenters. However, the transformation of modern construction materials, such as light steel, aluminum, and WPC, is gradually replacing the role of wood in structural work. This has reduced the scope of work for pre-construction carpenters, so a solution is needed to maintain the sustainability of their profession through post-construction work. This community service program is designed in response to this challenge through training in making smart furniture: functional, compact, and modern furniture relevant to the limited space needs of student boarding/rental housing around the State University of Malang campus. The activity methods include concept counseling, introduction to technical design (DED), and direct manufacturing practice in two partner workshops, namely the Revan Furniture and Indah Meubel wood workshops, each making smart furniture using different material variants (solid wood, Dutch teak, multiplex, and HPL finishing). The main work is a folding table and chair unit with dimensions of 120x100x90 cm that can be easily folded for minimalist housing needs. Evaluation of the training and outreach results showed a 45% increase in understanding of working drawings, a 20% increase in jointing skills, and a 20% increase in OSH awareness. This product meets three key criteria for engineered furniture: functionality, ease of use, visual appeal, and comfort. In conclusion, this training enhanced the carpenters' technical capacity and opened up new economic opportunities in the adaptive furniture sector..ABSTRAKWilayah Sukun, Lowokwaru, dan Karangbesuki di Kota Malang dikenal sebagai penyedia pekerja konstruksi, proporsi terbanyak adalah tukang kayu. Namun, transformasi material konstruksi modern seperti penggunaan baja ringan, aluminium, dan WPC, secara bertahap menggantikan peran kayu dalam pekerjaan struktur. Hal ini berdampak pada berkurangnya ruang lingkup kerja tukang kayu pra-konstruksi, sehingga diperlukan solusi untuk mempertahankan keberlangsungan profesi mereka melalui pekerjaan pasca-konstruksi. Program pengabdian ini dirancang sebagai respon atas tantangan tersebut melalui pelatihan pembuatan smart furniture: furnitur fungsional, ringkas, dan modern yang relevan dengan kebutuhan ruang terbatas pada hunian kost/kontrak mahasiswa di sekitar kampus Universitas Negeri Malang. Metode kegiatan meliputi penyuluhan konsep, pengenalan desain teknis (DED), hingga praktik pembuatan langsung di dua bengkel mitra, yaitu bengkel kayu Revan Furnitur dan Indah Meubel, pembuatan smart furniture masing-masing menggunakan varian material berbeda (solid wood, jati belanda, multiplek, dan finishing HPL). Karya utama berupa unit meja-kursi lipat berdimensi 120×100×90 cm yang dapat dilipat secara mudah untuk kebutuhan hunian minimalis. Evaluasi hasil pelatihan dan penyuluhan menunjukkan peningkatan pemahaman gambar kerja sebesar 45%, keterampilan kerja sambungan sebesar 20%, dan kesadaran K3 naik sebesar 20%. Produk ini memenuhi tiga dari empat kriteria utama furnitur teknik: fungsionalitas, kemudahan penggunaan, daya tarik visual, dan kekurangan adalah kenyamanan. Kesimpulannya, pelatihan ini meningkatkan kapasitas teknis tukang kayu, dan membuka peluang ekonomi baru dalam sektor furnitur adaptif.